PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING DALAM MENINGKATKAN EFEKTIVITAS BELAJAR SISWA KELAS XI IPS PADA MATA PELAJARAN EKONOMI DI SMA MUHAMMADIYAH 4 KOTA BENGKULU - Andriani, Melatiana; Suharmi, Suharmi; Zufiyardi, Zufiyardi (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
This study aims to determine that the application of the problem based learning (PBL) learning model can improve the effectiveness of learning for class XI IPS students in economics subjects at SMA Muhammadiyah 4 Bengkulu City. This type of research is classroom action research (PTK). Data collection techniques by conducting observations and documentation. Based on the results of the study, it is evident from the results of cycle I that the average effectiveness of student learning is only 29.12 with sufficient criteria and the results of cycle II, the average effectiveness of student learning only increased to 44.18 with good criteria and the results of the analysis that have been carried out using the t test at a significant level and degrees of freedom 15 indicate that t count = 4.71 ≥ t table 2.131 means that there is a significant increase in student learning effectiveness from cycle I to cycle II. So it can be concluded that the application of the problem based learning (PBL) learning model can improve student learning effectiveness.